FINANCIAL PERFORMANCE ANALYSIS AT MICROFINANCE INSTITUTIONS: CASE STUDY AT REGIONAL BUSINESS ENTITIES BOGOR REGENCY - Noviar, Yan; Hasrul, Hasrul; Herman, Herman (International Journal of Economy, Education and Entrepreneurship (IJE3), 2025)
Regional Business Entities (BUMD) are business entities whose capital is wholly or largely owned by the regional government. They consist of regional public companies and regional limited liability companies. Bogor Regency has several regional business entities (BUMD) operating in various sectors, including strategic sectors requiring government regulation and commercial sectors not explicitly regulated. Microfinance Institutions (LKM) are financial institutions that provide business development and community empowerment services through loans or financing micro-scale businesses to members and the community. PT Microfinance Institution (PT LKM) Bogor is a company originating from the Bogor District Credit Union (PD. PK), by applicable regulations, and its legal form has become PT LKM Bogor. PT LKM Bogor is at Jalan KSR Dadi Kusmayadi No. 6B Ruko Citra Nusa, Cibinong, Bogor Regency. This research aims to know the development of PT LKM's performance and its problems. The method for evaluating the performance of BUMD PT LKM Bogor was carried out based on assessing the health aspects of the DIR Decree Number 30/SK/KEP/DIR dated 30 April 1997 concerning Procedures for Assessing the Health Level of Rural Banks. It was guided by the Decree of the Minister of Finance of the Republic of Indonesia No. 826/KMK.013/1992. The aspects assessed in determining the level of company health include capital, productive asset quality, management, profitability, and liquidity. Based on the results and discussion above, the conclusions of this research are as follows: PT LKM's performance from 2018-2022 shows UNHEALTHY conditions. One of the reasons why PT LKM's health value is so small is that the quality of its productive assets, which have the most significant weight in determining the company's health level, has very little value.